Estimation and use of modified prior probabilities for digital classification improvement of tropical forests - Pedroni, Lucio (CATIE, Turrialba (Costa Rica), 2014)
Tesis (Ph. D.) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), 2000